การศึกษาอิทธิพลปัจจัยเชิงสาเหตุของความขัดแย้งระหว่างงานกับครอบครัว ที่ส่งผลต่อความตั้งใจที่จะเปลี่ยนงาน และคุณภาพชีวิตของพนักงานคุมประพฤติ - สังข์แก้ว (Thoungtong Sungkaew) ตวงทอง; โยเหลา(Dusadee Yoelao) ดุษฎี; ศุภฤกษ์ชัยสกุล(Numchai Supparerkchaisakul) นำชัย (Journal of Behavioral Science for Development, 2016)
(The Study of Effects of Causal Modeling of Work-Family Conflict Affecting Satisfaction, Intention to Leave and Quality of Life among Probation Officers) Abstract This study aimed to investigate the indirect effect of causes and satisfaction, quality of life and intention to leave on work-family conflict and to study moderator effect of coping influence the strength of the relationship between work-family conflict and satisfaction among probation officers. The sample of 769 probation officers from Department of Probation, Ministry of Justice. There are 4 groups of variables in this study. First, the 2 work-family conflict variables were family interference with work (FIW) and work interference with family (WIF). Secondly, the 5 cause variables were family support, family type, role salience, perfectionism and psychological capital. Next, 4 affect variables were family satisfaction, job satisfaction, intention to leave and quality of life. Finally, moderator was coping. Path analytic results showed that perfectionism and psychological capital indirectly affected quality of life, family satisfaction and job satisfaction via WIF, role salience indirectly affected job satisfaction via WIF, perfectionism and psychological capital indirectly effected intention to leave via FIW, and coping was not influence the relationship between work-family conflict in both directions and both family and work satisfaction. Keywords: work-family conflict, causes, quality of life, intention to leave, coping, probation officer